Sustainable fashion - Gómez, María Del Lourdes Arias; Gómez, Jesús Arias; Blanco, Azalea María Peña; Arteaga, Lorena Gabriela Hernández; Torres, Lilian Esperanza Rodríguez; Segovia, Lourdes Leticia Cárdenas; Aguilar, Simón Armando Rincón (Seven Editora, 2023)
The constant change of trends, we see it in the fashion week shows of Paris, New York, Madrid, Milan, etc., each show is more extravagant than the other.  Internationally recognized brands work with haute couture dresses, which aggravate environmental pollution because they cannot be sold at a lower price or in discount stores, therefore, clothing factories make clothes for different social classes, obviously, with sales for haute couture dresses, they do not pay the production costs. Committing to responsible consumption means knowing the manufacturing process and the employment situation of the workers who make them, because in many countries (Mexico, China, Italy, among others) seamstresses and tailors have undignified salaries, working hours and benefits.  General objective: To explain the relationship between clothing consumption and environmental damage. In addition, we emphasize sustainability in all aspects of life, for the sake of our students, their families, and the environment. DOI:https://doi.org/10.56238/sevened2023.006-072